2018
DOI: 10.3892/ijo.2018.4346
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of E‑cadherin expression mediated by a novel dsRNA suppresses the growth and metastasis of bladder cancer cells by inhibiting β-catenin/TCF target genes

Abstract: Low expression levels of E-cadherin are correlated with poor prognosis in patients with bladder cancer (BCa). A small activating RNA (saRNA) targeting a specific promoter region can activate gene expression. In the present study, two small double-stranded RNAs (dsRNAs) targeting the promoter region of human E-cadherin were designed and synthesized, and the regulatory role of saRNAs in E-cadherin expression was investigated. The results of reverse transcription-quantitative polymerase chain reaction and western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…37 Under conditions of strong adhesion, b-catenin is stable and protected within the cadherin complex, forming a strong coupling structure and maintaining tight cell junctions. 36,38,39 Our study found that E-cadherin was degraded under elevated glucose, but the b-catenin in the cytoplasm did not increase. According to previous studies, there are two metabolic pathways after b-catenin is isolated from b-catenin/E-cadherin complex: 40,41 and differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…37 Under conditions of strong adhesion, b-catenin is stable and protected within the cadherin complex, forming a strong coupling structure and maintaining tight cell junctions. 36,38,39 Our study found that E-cadherin was degraded under elevated glucose, but the b-catenin in the cytoplasm did not increase. According to previous studies, there are two metabolic pathways after b-catenin is isolated from b-catenin/E-cadherin complex: 40,41 and differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…CDH1 is a TSG that has gained attention for its potential to be upregulated using saRNAs and has been investigated in this context across many cancer types. 2 , 23 , 24 , 25 , 26 , 27 CDH1 encodes the transmembrane glycoprotein E-cadherin, which is involved in maintaining epithelial cell morphology via adherens junction connections. 67 Furthermore, E-cadherin is anchored to the cell’s cytoskeleton via an interaction with β-catenin, a key protein involved in the pro-proliferative Wnt signaling pathway.…”
Section: Different Approaches To Restoring Tumour Suppressor Functionmentioning
confidence: 99%
“…(Refs. 2 , 23 , 24 , 25 , 26 , 27 ) VEZT Vezatin, adherens junctions transmembrane protein Transmembrane protein involved in maintaining adherens’ junctions. Gastric cancer In vitro Xie et al.…”
Section: Introductionmentioning
confidence: 99%